ANALYSIS OF PRICE MANIPULATION IN THE SPICE TRADE IN BARUS DISTRICT WAHBAH AZ-ZUHAILI'S PERSPECTIVE - Al Anshori Akbar Sigalingging; Rahmat Hidayat (Program Pascasarjana UIN Sumatera Utara, 2025)
This study analyzes the practice of price manipulation in the spice trade at Barus Market, one of Indonesia's oldest spice ports, through the lens of Islamic economic principles according to Wahbah Az-Zuhaili. The manipulation includes price manipulation and artificial stock withholding, driven by information asymmetry between sellers and less-informed buyers, particularly from outside the region. Employing a descriptive qualitative and empirical juridical approach, data were collected through interviews, direct observation, and literature review. Findings reveal that such practices violate fundamental Islamic trade ethics, including shidq (honesty), ‘adl (justice), and prohibitions against tadlis (fraud) and gharar (uncertainty). Az-Zuhaili advocates for state intervention through price regulation (tas'îr) in cases of market distortion caused by merchant misconduct. The study highlights the need for sharia-based market reform, consumer protection via khiyar ghabn, and ethical education for traders to realize a fair, transparent, and Islamic economy.